2018
DOI: 10.1088/1361-648x/aae21d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic impurity in topological nodal loop semimetals

Abstract: We investigate the Kondo effect of a spin-1/2 magnetic impurity in a topological nodal loop semimetal, in which band touchings form a nodal loop. The Fermi surface of a nodal loop semimetal is a torus or a drum-like structure, which is determined by chemical potential. When the chemical potential μ lies at the nodal loop ([Formula: see text]), the magnetic impurity and the conduction electrons form bound states only if their coupling exceeds a critical value. As the chemical potential is tuned away from the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…This behavior is independent of the chemical potential and DOS, and is also independent of real space axis directions. The r −3 decay behavior in our type-II NLSM Hamiltonian is qualitatively consistent with the results obtained in the type-I case, [40] considering that the dispersion relation contains quadratic terms along the k z -axis. However, the r −2 decay rate observed in the hybrid NLSM is much distinct from the type-I and type-II cases.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This behavior is independent of the chemical potential and DOS, and is also independent of real space axis directions. The r −3 decay behavior in our type-II NLSM Hamiltonian is qualitatively consistent with the results obtained in the type-I case, [40] considering that the dispersion relation contains quadratic terms along the k z -axis. However, the r −2 decay rate observed in the hybrid NLSM is much distinct from the type-I and type-II cases.…”
Section: Discussionsupporting
confidence: 88%
“…The Kondo effect of a single magnetic impurity in a type-I NLSM has been studied, and it has been reported that when the chemical potential lies at the nodal loop, the magnetic impurity and the conduction electrons form bound states only if their coupling exceeds a critical value and the spatial decay ratio is either proportional to 1/r 2 or 1/r 3 , depending on the real space directions. [40] Distinct from the type-I case already studied, in the hybrid and type-II NLSMs discussed in this paper, the DOS is always significant, so the magnetic impurity and the conduction electrons always form bound states. The DOS of the hybrid case is much larger than that of the type-II case, so in general the binding energy takes larger values in the hybrid case.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…To this regard, the analysis of how these materials behave in presence of impurities becomes essential. In this context, several studies have been conducted in Weyl, Dirac, nodal loop and triple-component semimetals [12][13][14][15][16][17][18][19][20][21][22][23] and topological insulators [24][25][26][27][28][29][30][31][32][33][34], where signatures of the Kondo effect are observed, the appearance of resonances is displayed and the stability of these materials against impurities is discussed. In this work, we will work along the lines of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The variational method we apply has been used to study the ground state of the Kondo problem in normal metals, 44,57 antiferromagnet, 58 2D helical metals, 53 and various novel topological materials. 56,[59][60][61][62] The paper is organized as follows. We present the model Hamiltonian, dispersion as well as the electron and hole pockets at the Fermi level in Sec.…”
Section: Introductionmentioning
confidence: 99%